Elizabeth I and religion, 1558-1603 - Doran, Susan (Lancaster pamphlets., 1994)
Susan Doran describes and analyses the process of the Elizabethan Reformation, placing it in an English and a European context. She examines the religious views and policies of the Queen, the making of the 1559 settlement and the resulting reforms. The changing beliefs of the English people are discussed, and the author charts the fortunes of both Puritanism and Catholicism. Finally she looks at the strengths and weaknesses of Elizabeth I as royal governor, and of the Church of England as a whole.